Agir jornalístico em cenários de crise humanitária: narrativas compreensivas orientadas para a paz - Abib, Tayane (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
Beyond the hegemonic model of news reporting, I commit myself to propose narrative ways for journalistic coverage in a context of Antioquia220humanitarian crisis. I thus propose to approximate the study fields of comprehension and communication for constructing a culture of peace, in order to highlight the possibilities of dialogical reporting, sensible to the realities of men and women afflicted by such crises. In order to elucidate my reflections, I point out this approach on the narratives about Africa written by Portuguese reporter Paulo Moura and Spanish reporter Bru Rovira.